Organophosphate esters inhibit enzymatic proteolysis through non-covalent interactions - Zeming Wang; Wei Zhang; Xiaojie Hu; Yanzheng Gao (Environment International)
Enzymatic proteolysis is the key process to produce bioavailable nitrogen in natural terrestrial and aquatic ecosystems for microorganisms and plants. However, little is known on how protein degradation is influenced by organic contaminants. As we known, the overuse of organophosphate esters (OPEs) has caused serious pollution in soil, water, and sediment. Thereby we studied the effect of OPEs on the proteolysis of protein GB1 in aqueous system at neutral pH, and explored the underlying molecular mechanism. Colorimetric ninhydrin methods and SDS-PAGE results revealed that OPEs inhibited the enzymatic hydrolysis of protein GB1. Based on fluorescence quenching experiments, the binding constant (LogKA) were found in order: 6.16 (dibutyl phosphate) > 5.11 (diethyl phosphate) > 1.78 (tributyl phosphate) > 0.876 (triethyl phosphate), proving the interactions between OPEs and protein GB1. Further spectroscopic experiments and molecular docking simulations showed that OPEs could entered the pocket structure of GB1 and induced secondary structural changes and protein folding through non-covalent interactions dominated by hydrogen bonding and van der Waals forces. In addition, organophosphate diesters (di-OPEs) and long-chain OPEs had stronger affinity to GB1, due to the more negative and denser electrostatic surface potential distributions. The deformation of proteins hindered the contact between their active sites and enzymes, leading to the inhibition of GB1 hydrolysis. This study deepened our understanding of the effect of OPEs on protein transformation and degradation, which could further influence the ecological functions and nutrient cycling.